Effects of bariatric surgery on untreated lower urinary tract symptoms: a prospective multicentre cohort study. (8th December 2014) - Luke, Serge; Addison, Ben; Broughton, Katherine; Masters, Jonathan; Stubbs, Richard; Kennedy‐Smith, Andrew
<x xml:space="preserve">Abstract</x> Objective To evaluate the effects of bariatric surgery on lower urinary tract symptoms (LUTS) in a prospective cohort study. Patients and Methods Patients undergoing bariatric surgery were recruited into the study. LUTS were assessed using the International Prostate Symptoms Score (IPSS) in men and Bristol Female Lower Urinary Tract Symptoms Score Questionnaire (BFLUTS) in women. Serum glucose, insulin and prostate‐specific antigen (PSA) levels were recorded; insulin resistance was quantified using the Homeostasis Model Assessment (HOMA‐IR) method. Patients were assessed before surgery, and at 6–8 weeks and 1 year after surgery. Weight loss, change in body mass index (BMI), total symptoms score as well as individual symptoms were tested for statistical significance with correction for multiple testing using Bonferroni method. Linear regression analysis was performed with total symptoms score change at 1 year as the outcome variable and BMI, age, total symptoms score before surgery, HOMA‐IR, glucose level before surgery, insulin level before surgery, change in insulin level after surgery, weight loss and BMI loss as predictor variables. Results In all, 86 patients were recruited and 82% completed at least one follow‐up after surgery. There was significant weight loss and reduction of BMI after surgery (P < 0.001). At 6 weeks, there was a significant reduction in overall symptom score (P < 0.001) and this improvement was sustained at 1 year. Linear regression analysis showed that total symptoms score at baseline, HOMA‐IR, preoperative insulin level and change in insulin level postoperatively were predictive of the change in total symptoms score while the amount of weight loss was not. Conclusions The study confirms the improvement in LUTS after weight loss but there is no correlation between the improvement and the time course or degree of weight loss. Rather there is a suggestion that the improvement in symptoms is linked to improvement in insulin resistance seen as a result of both bariatric surgery and weight loss.